Relationship between Malocclusion and Oral Health-Related Quality of Life among High School Students - Mashallah Khanemasjedi; Marzieh Araban; Mehdi Mohamadinia (Journal of Education and Community Health)
Background and Objective: Currently, the effect of oral and dental condition on patients' quality of life and daily activities is an important issue in dentistry. Regarding this, the present study aimed to evaluate the relationship between malocclusion and oral health-related quality of life among high school pupils in Ahvaz, Iran. Materials and Methods: This cross-sectional study was conducted on 192 high school students (age range: 14-18) in Ahvaz city in 2016. The study population was selected through random multi-stage cluster sampling technique. Data collection tools included a demographic questionnaire, Oral Impact on Daily Performance, and Index of Orthodontic Treatment Need (IOTN). The data were analyzed in SPSS (version 22) using the Spearman correlation test and One-way ANOVA. Results: The mean quality of life was obtained as 6.48±19.47. The results demonstrated that the oral and dental conditions of 26.6% of the participants affected their quality of life. Oral condition was found to mostly affect smiling (15.6%), followed by emotional situations (9.9%). There was no significant relationship between the mean oral health-related quality of life score and the dental health component of IOTN (P=0.130). However, a significant correlation was observed between the oral health-related quality of life and the aesthetic component of IOTN (P=0.004). Conclusion: As the findings of the present study indicated, the high school students did not have a favorable oral health-related quality of life. Given the importance of oral and dental health in improving the overall quality of life, it is recommended to consider the various social and psychological impacts of oral and dental health in the delivery of dental services to enhance the overall quality of life in the community.